PENGEMBANGAN E-LKPD PEMBELAJARAN IPAS MENGGUNAKAN WEBSITE WIZER ME BERBASIS RADEC BERBANTUAN MIND MAP DI KELAS IV SD - Nadiva Putri Ananda; Risda Amini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the gap in conditions that researchers found in the field, that educators still use LKPD in simple forms such as sheets containing questions so that the LKPD provided is less interesting for students, coupled with the lack of use of technology in working on LKPD is also very unfortunate considering that education always goes hand in hand with technology. This study aims to develop E-LKPD for science learning using the Wizer.me website based on RADEC assisted by Mind Maps in Grade IV of Elementary School that is valid and practical. This study uses the R&D research type. With the ADDIE development model with the stages of Answer, Design, Development, Implementation, and Evaluation. Based on the validity test results by material, language, and media experts, the developed E-LKPD is categorized as very valid, with an average rating of 95.16%. The trial activities were carried out at SD Negeri 09 Koto Pulai and SD Negeri 16 Pulau Karam, while the implementation was carried out at SD Negeri 22 Duku. The practicality test involving teachers and students at the trial and research schools showed that this E-LKPD is very practical to use in learning. If averaged overall from all schools, the percentage of practicality of the E-LKPD reached 98% from teachers and 94.28% from students. Thus, it can be concluded that the E-LKPD for learning science using the Wizer.me website based on RADEC assisted by Mind Maps in Grade IV elementary school is proven to be very valid and practical to use in learning.